Designing and Developing an Educational-Therapeutic Game for Improving Healthy Lifestyle in Children and Adolescents - Fatemeh Azizi-Soleiman; Motahar Heidari-Beni; Zeinab Hemati; Roya Kelishadi (International Journal of Computer Games Technology)
Educating healthy lifestyle behaviors through game can help children and adolescents achieve healthy habits. The aim of the present study was to develop a game to promote children’s and adolescents’ lifestyle behaviors. The “Toward Health” is a board game designed by a multidisciplinary team consisting of nurses, nutritionists, physical activity experts, pediatricians, pediatric psychologists, graphic artists, and experts in designing board games to help children adopt healthy eating and sleep habits and become physically more active. Players move their tokens based on the number of squares indicated by a dice rolled. If a player’s token lands on the square containing questions or points related to a healthy lifestyle, he/she must answer the question or read the point loudly. If answers to the questions are correct, the player takes the card. Interventional studies are recommended to confirm the potential of these games in preventing and/or treating childhood obesity. In the future, we are going to assess the validity and acceptance of the game in various age groups.